Positive links between student participation, recognition and wellbeing at school. (2022) - Anderson, Donnah L.; Graham, Anne P.; Simmons, Catharine; Thomas, Nigel Patrick
Highlights: Student participation was measured using a newly validated, multidimensional scale. Student participation was positively and strongly related with wellbeing at school. Simply having 'voice' did not significantly predict wellbeing. More authentic forms of participation significantly predicted wellbeing. Recognition mediated the participation-wellbeing relationship. Abstract: Recent years have seen increased attention paid to both student participation and wellbeing at school. Little research to date has investigated the extent to which participation is associated with wellbeing, let alone which specific elements of participation may predict wellbeing. This paper reports the quantitative phase of a mixed-methods study investigating these associations. Students ( N  = 1, 435) from Government and Catholic high schools in New South Wales, Australia, completed an online survey. Hierarchical regression analyses showed that having a say with influential people, having choice, having influence, and working together significantly and positively predicted wellbeing. Simply having 'voice' did not significantly predict wellbeing. Mediation analyses showed that student participation fostered recognition – giving and receiving care, respect and valuing others – which in turn fostered wellbeing. The results suggest schools endeavouring to strengthen student wellbeing would benefit from identifying whether and how participation initiatives create the conditions for recognition to occur.